The Prevalence and Outcomes of Hepatorenal Syndrome in Chronic Liver Disease Patients in a Tertiary Care Hospital : Hepatorenal Syndrome in Chronic Liver Disease - Ali, Rubiya; Goswami, Mansi; Talpur, Mir Tahir Hussain; Naeem, Muniba; Kumar, Sunil; Malik, Farah; Ghimire, Samir; Aslam, Neha; Hasan, Mohammad (Pakistan Journal of Health Sciences, 2023)
Hepatorenal syndrome (HRS) leads to a severe kidney injury leading to its eventual failure in the background of chronic liver disease. Objective: This research’s objective was to define the frequency of hepatorenal syndrome (HRS) in the background of cirrhosis and to find out the outcomes of the patients with HRS. Methods:This is a detailed prospective clinical series research. It was conducted in the Department of Medicine, Jinnah Postgraduate Medical Center (JPMC), Pakistan, from February 2020 to December 2020 after approval by the authorized review board. Jinnah Postgraduate Medical Center (JPMC). A sample size of 101 was calculated. The lab values including prothrombin time (PT), serum albumin, and chronic liver disease variations were established for confirmative diagnosis. Frequency tables were created for parameters to be determined (sex and Child-Pugh classification). The means and their SD of parameters of interest (age and weight) were calculated. Results:The demographic variables were the mean age of the patients was 62.5±10.2 and the mean bilirubin was 2.32 ± 2.3mg/dL. 68 (67.3%) of the patients had normal creatinine and 33 (32.7%) of the patients had raised serum creatinine. 2(10.5%) of the patients had a numerical score of 5-6, 13 (68.4%) of the patients had a total score of 7-9 and 4(21.1%) of the patients had 10-15 scores. Hepatorenal syndrome was detected in 11.9% of patients with cirrhosis, among whom 4 (33.3%) died. Conclusions:The hepatorenal syndrome is quite common in liver diseases and it needs to be assessed.